Kiblat dan Perubahan Persepsi Sosial Pasca Gempa Tahun 2004 di Indonesia - Siregar, Muhammad Habibi; Muhammad, Muhammad (Jurnal Pemberdayaan Masyarakat, 2024)
This study illustrates the reality of differing perceptions within society regarding the direction of the qibla, which has been influenced by the shifting of the Earth caused by several earthquakes that have struck Indonesia. The research employs a phenomenological approach linked to ritual theory, highlighting a strong relationship between spiritual symbols and the behavior of communities who feel connected to these symbols. This situation can also have multiple effects on other fields of study.The researcher found that the emotional attachment of the Muslim community to spiritual symbols, such as mosques, has different implications when faced with the issue of the qibla direction shifting due to recent earthquakes in Indonesia. These implications can be categorized into two aspects: substance and essence."Substance" refers to those who believe that the qibla direction, assumed to have changed due to advances in scientific knowledge, must be adjusted to align with the latest developments. Meanwhile, "essence" pertains to those who consider the qibla direction merely a symbol and therefore see no need to physically shift mosques or other structures, as it could lead to more significant social impacts. This view is based on the concept of "amal jariah" (continuous charity), which could be affected by changes or renovations to mosques.This research is valuable not only for providing peace of mind in worship by ensuring prayer is conducted in the correct qibla direction but also for educating the public about how technological advancements can help in determining a more accurate qibla direction.